SALESFORCE END-TO-END IMPLEMENTATION HANDBOOK a practitioner's guide for setting up programs and projects to deliver superior business outcomes - Jørgensen, Kristian Margaryan (PACKT PUBLISHING LIMITED, 2023)
Packed with practical examples, case studies, and proven recommendations, this handbook helps you manage enterprise-grade Salesforce programs Key Features Explore the end-to-end Salesforce implementation lifecycle with templates and practical examples Discover common issues and strategies for mitigation and prevention Work with checklists to assess the state of your Salesforce implementation in each phase Purchase of the print or Kindle book includes a free PDF eBook Book Description With ever-growing digital transformation programs involving Salesforce, there is a greater need for a comprehensive overview of the phases and activities specific to Salesforce implementations. This book will act as a detailed guide for your Salesforce implementation journey, including common issues and pitfalls to mitigate and prevent errors. The Salesforce End-to-End Implementation Handbook starts with the pre-development phase. Here you'll understand how to define the vision and nature of your project, determine your change management strategy and delivery methodology, learn to build a business case for your project, get insights on engaging with Salesforce and implementation partners, and learn to establish a governance framework. As you progress, you'll gain insights on the necessary activities, milestones, and common issues faced in salesforce implementation, along with strategies to mitigate them. At the end of each section, you'll find evaluation checklists to assess the state of your Salesforce implementation. By the end of this book, you'll be well-equipped to set up Salesforce projects and programs effectively and deliver maximum ROI. What you will learn Discover the critical activities in Salesforce implementation Address common issues faced in implementing Salesforce Explore appropriate delivery methodology Understand the importance of a change management strategy Govern Salesforce implementation through all its phases Gain insights on key activities in the continuous improvement phase Leverage customer 360 for analytics, AI and automation Who this book is for This book is for salesforce consultants, architects, project/program managers, delivery leaders for salesforce implementation, or product owners- planning to implement Salesforce or already implementing Salesforce for their organizations. If you are switching to a role in salesforce development, this book will act as a guide on what to expect on the job and how to ace it. Familiarity with basic business, CRM, and project management concepts is required.
Keywords: Salesforce (Online service); Sales management; Customer relations -- Management; Salesforce (Serveur); Ventes; Gestion; Customer relations; Management